Analysis of Added Value of Bamboo into Woven Bamboo Products in Punggawukawu Village, Benua District, South Konawe Regency (Case Study of the Narti Sekar Craft Business Group) - Ayu, Ni Gusti Ayu Ketut Sulastri; Ilma Sarimustaqiyma Rianse; Fahria Nadiryati Sadimantara (International Journal of Technology and Education Research, 2023)
This study analyzes the process of making woven bamboo products and calculates the amount of added value resulting from the process of making woven bamboo in Punggawukawu Village, Benua District, South Konawe Regency. The types of data used in this study were primary data and secondary data. Primary data were obtained through interviews while secondary data were obtained from various references related to literature related to this research. This research was conducted from November 2022 to March 2023. The determination of the research location was purposive and the method used in this research was the Case Study method. This study was analyzed using a qualitative descriptive method and the Hayami method. The results of this study indicate that 1) The process of processing bamboo into hats includes the process of cutting bamboo, cleaning, splitting, drying, drying, plaiting, and installing woven head mats, bamboo around the hat, and plastic and the processing of bamboo into tampah/nyiru includes cutting bamboo, cleaning, splitting, smoothing bamboo, plaiting, and installing the rim of tampah bamboo. 2) The added value resulting from the processing of bamboo into Tampah/Nyiru and Caping Caps is IDR 18,461/unit of raw material and IDR 62,957/unit of raw material respectively with value added ratios of 76.92% and 94, respectively 43%. Of the two processed products that provide the greatest added value is Caping Caps while the smallest is woven products